Latest Carboniferous (Late Gzhelian) Fusulinids from Timor Leste and their Paleobiogeographic Affinities. (May 2014) - Davydov, Vladimir I.; Haig, David W.; McCartain, Eujay
Abstract : An uppermost Gzhelian bioherm discovered in the central highlands of Timor Leste contains abundant foraminifera belonging to 17 genera. Representatives of the families Biseriamminidae, Biwaellidae, Bradyinidae, Cornuspiridae, Lasiodiscidae, Palaeotextulariidae, Pseudotaxidae, Ozawainellidae, Schubertellidae, Schwagerinidae, Staffellidae and Textrataxidae are present, including 21 species referred to known types and 12 species left in open nomenclature. Two new Schwagerina species are described: Schwagerina timorensis new species, and Schwagerina maubissensis new species. The assemblage belongs to the uppermost Gzhelian Schwagerina robusta–Ultradaixina bosbytauensis Zone although a possible lowest Asselian correlation cannot be excluded (the name Ultradaixina is controversial and sometimes synonymized as Bosbytauella . The case to resolve this issue has been submitted to the Bulletin of Zoological Nomenclature). The bioherm is the oldest carbonate unit so far recorded from the Maubisse Formation and the oldest sedimentary unit biostratigraphically dated in Timor. This discovery has implications for the latest Carboniferous–earliest Permian climate history of Timor that lay in the northern part of the north-south East Gondwana rift system along which the western margin of Australia later developed. The highest peak in fusulinid diversity within the Pennsylvanian–Cisuralian interval and a major marine transgression documented in many regions in Northern Pangaea took place during the latest Gzhelian to earliest Asselian and evidence for this is now extended to southern Pangaea. Cluster analysis, using the Jaccard similarity index at species level, of late Gzhelian fusulinids from 16 regions has been performed. This shows that the Timor fauna is most closely related to faunas from South China and the Changning-Menlian region of Yunnan (China). The assemblages here are distinct from those of three biogeographic regions (Arctic, Uralo-Asian and Irano-Taurids) recognized within the Tropical belt.